Depression and Temporal Lobe Epilepsy: Expression Pattern of Calbindin Immunoreactivity in Hippocampal Dentate Gyrus of Patients Who Underwent Epilepsy Surgery with and without Comorbid Depression. (2nd May 2019) - D'Alessio, Luciana; Konopka, Hector; Solís, Patricia; Scévola, Laura; Lima, Mónica Fernandez; Nuñez, Claudio; Seoane, Eduardo; Oddo, Silvia; Kochen, Silvia
Abstract : Purpose . Changes in calbindin (CB) expression have been reported in patients with temporal lobe epilepsy (TLE) with controversial implications on hippocampal functions. The aim of this study was to determine the CB immunoreactivity in hippocampal dentate gyrus of patients who underwent epilepsy surgery for drug-resistant TLE with and without comorbid depression and/or memory deficits. Methods . Selected hippocampal samples from patients with TLE who underwent epilepsy surgery were included. Clinical and complementary assessment: EEG, video-EEG, MRI, psychiatric assessment (structured clinical interview, DSM-IV), and memory assessment (Rey auditory verbal learning test, RAVLT; Rey-Osterrieth complex figure test, RCFT), were determined before surgery. Hippocampal sections were processed using immunoperoxidase with the anti-calbindin antibody. The semiquantitative analysis of CB immunoreactivity was determined in dentate gyrus by computerized image analysis (ImageJ). Results . Hippocampal sections of patients with TLE and HS (n = 24 ) and postmortem controls (n = 5 ) were included. A significant reduction of CB+ cells was found in patients with TLE (p < 0.05, Student'st -test). Among TLE cases (n = 24 ), depression (n = 12 ) and memory deficit (n = 17 ) were determined. Depression was associated with a higher % of cells with the CB dendritic expression (CB-sprouted cells) (F 1, 20 = 11.81, p = 0.003, h p 2 = 0.37 ), a higher CB+ area ( μ m 2 ) (F 1, 20 = 5.33, p = 0.032, h p 2 = 0.21 ), and a higher optical density (F 1, 20 = 15.09, p = 0.001, h p 2 = 0.43 ) (two-way ANOVA). The GAF scale (general assessment of functioning) of DSM-IV inversely correlated with the % of CB-sprouted cells (r = − 0.52, p = 0.008 ) and with the CB+ area (r = − 0.46, p = 0.022 ). Conclusions . In this exploratory study, comorbid depression was associated with a differential pattern of CB cell loss in dentate gyrus combined with a higher CB sprouting. These changes may indicate granular cell dysmaturation associated to the epileptic hyperexcitability phenomena. Further investigations should be carried out to confirm these preliminary findings.